Effect of feeding system and fermented sago waste on performance of broiler chicken - Kompiang, I Putu; ., Supriyati (Indonesian Journal of Animal and Veterinary Sciences, 2001)
An experiment, with a split plot experimental design, was conducted to determine the effect of feeding system (full vs choice feeding) and fermented sago waste (AST 5 vs 0%) on the performance of broiler chickens. Complete feed was formulated tocontain 21% crude protein, 2900 kcal ME/kg, without or with 5% AST. Feed for choice feeding was formulated to contain 2900 kcal ME/kg, without or with 5% AST with crude protein 23 or 17%. Four hundreds DOC broilers were used for each treatment divided into 4 replicates (100 birds/replicate) on litter system. Feed and water were given ad lib. during the 4 weeks trial. Data collected included feed consumption (weekly), body weight (bi-weekly), feed conversion ratio (FCR) and protein efficiency ratio (PER) were calculated biweekly. Feeding system has no significant effect on total feed/energy consumption. Choice feeding reduced total protein consumption (P<0.01; 323.5 vs 354.9 gram/head/4weeks), increased body weight gained (P<0.01; 889.5 vs 835 gram/head/4weeks), improved FCR (P<0.05; 1.90 vs 2.03), and PER (P<0.001; 0.37 vs 0.43). Fermented sago waste (AST) had no significant effect on total feed/energy consumption (P<0.05), reduced total protein consumption (P<0.05; 333.6 vs 349.8 gram/head/4weeks), increased body weight gained (P<0.05; 887.5 vs 837 gram/head/4weeks), improved FCR (P<0.05; 1.88 vs 2.06) and PER (P<0.05; 0.38 vs 0.42). It is concluded that broiler chicken had an ability to determine its protein requirement, and AST supplementation significantly improved performance of the birds. Â  Key words: Choice feeding, fermented sago waste, broiler, FCR, PER